DISCUSSION ON “COMPETITIVE SORPTION OF MULTIPLE COMPONENT HEAVY METALS FROM GOLD MINING LEACHATE ONTO LATERITE SOIL” LOWLAND TECHNOLOGY INTERNATIONAL, 10(1), 54-64 - Z. Li; X. Tang (International Association of Lowland Technology, 2009)
After going through the paper written by A. Putthividhya published in Lowland Technology International 10(1) 54-64, we found that there are some points in the methodology and analysis of results necessary to be clarified. Whilst essentially the experimental approach was straightforward and sound, beyond this, however, the analysis and the interpretations drawn are far from satisfactory.